Trust: Apakah penting untuk meningkatkan continuance intention pada aplikasi ride hailing? - Prameswari Dinda; Kurniawati Kurniawati; Yolanda Masnita (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The ride-hailing industry is seen as a rapidly growing industry. The variety of ride hailing application brands in Indonesia proves the increasing business competition of the online transportation industry. Faced with these conditions, the ride hailing industry needs to provide services with different values than its competitors. This study was conducted to examine the role of value given by ride hailing applications to Satisfaction so as to achieve continuance intention by involving trust as mediation. The population in this study is all ride hailing application users in Indonesia. The sample in this study used 230 respondents who met the criteria of the researcher. Sampling in this study used a non-probability sampling method with purposive sampling techniques. The data analysis method used in this study was SEM with AMOS software. The results showed that hedonic value, price value, social value can positively affect satisfaction and continuance intention. The results of the study explain that trust can partially mediate the effect of satisfaction on continuance intention. Keywords: trust, satisfaction, continuance intention, perceived value, ride hailing application